Contributions to Higher Engineering Education (Springer Singapore, 2018)
The book focuses on teaching knowledge and principles (Higher Education) regarding professional practice of engineering (life and lifelong learning). It covers recent developments in engineering education. This book comprises the select proceedings of the conference organised by the Portuguese Society for Engineering Education. This book goes beyond the examination of the economic, culture, and social factors, which influence the education of engineers in different higher education institutions, and encompasses critical thinking and problem solving, communication, collaboration and creativity and innovation. These are essential components of engineering education. The contents of this book are useful to researchers and professionals engaged in the re-engineering of engineering education.